How far Kazzponic applied the concept of environmental marketing: a case study on Kazzponic Sdn Bhd / Wan Muhamad Khairuddin Wan Salim - Wan Salim, Wan Muhamad Khairuddin (2009)
The purpose of this paper is to study on how to have competitive environmental marketing concepts. This paper looks at the respond of Kazzponic in order to have effective and practice the environmental marketing concept. The findings reveal that there are several factors that can lead ineffective practice the concepts. The important is the process of environmental marketing model must well follow if want to be a green company. Finally, further studies and analysis should be undertaken and are recommended for enhance the practice.